Understanding the Cognitive Immersion of Hospitality Architecture in Culture and Nature: Cultural Psychology and Neuroscience Views - Xie, Haihui; Chen, Qianhu; Nespoli, Chiara; Riso, Teresa (Frontiers in Psychology, 2022)
Hotel architectural design plays a critical role in consumers’ hospitality experiences, and it is important to consider that people may have different aesthetic cognitions towards the sensory properties of nature (i.e. the hotel’s architecture), such as its colour and texture, as well as the landscape. While neuroaesthetics has emerged as a nascent field in hospitality research, few studies have investigated how nature reflects aesthetic experiences in the human brain. Moreover, the neuroaesthetic interpretation of architecture through the aesthetic triad is a novel interdisciplinary field. A field survey conducted at Amanfayun—a hotel in Hangzhou, China—in support of our propositions proves that sensory–motor, knowledge-meaning and emotion valuation systems play key roles in appreciating architectural aesthetics. This article demonstrates that the evaluation of fluency, complexity and naturalistic patterns of an architectural masterpiece is achieved through the sensory–motor systems. Our results also prove that familiarity, expectations, context and cultural background directly affect an individual’s aesthetic knowledge and meaning of architecture. Moreover, the interaction of sensory–motor and knowledge elements is uniformly moderated by the emotion valuation system, resulting in a balanced appreciation of aesthetic architecture. Lastly, the study reveals the central roles of culture and nature in cognitive rejuvenation.